Fasilitasi Kolaborasi Stakeholder Untuk Penanganan Darurat Sampah Di Kota Banjarmasin - sugi Sugiannor (Universitas Lambung Mangkurat, 2025)
AbstractThe city of Banjarmasin is currently facing a waste management emergency due to the closure of the Basirih Final Disposal Site (TPAS) in February 2025. This situation was exacerbated by the limited capacity of the Banjarbakula Regional Landfill to accommodate waste from the city, resulting in overflowing garbage at various sites. This community service program aimed to facilitate stakeholder collaboration through a pentahelix model (government, academia, community, private sector, and media) to identify problems, build shared understanding, and design a collaborative institutional model for emergency waste management. The main activity was a Focus Group Discussion (FGD) involving the Environmental Agency, the Green Community Forum, academics, small entrepreneurs, and media. The results revealed an initial commitment among parties to draft a Policy Brief proposing a permanent Pentahelix Collaboration Forum for waste management. The program also produced media coverage, educational videos, and strategic recommendations for local government. This collaborative model demonstrates effectiveness in fostering cross-sector synergy toward resilient and sustainable waste governance.Keywords: stakeholder collaboration, pentahelix, waste management, facilitation, Banjarmasin